ANALYSIS OF CONVERGENCE BETWEEN PROVINCES IN INDONESIA - Kartini Kartini; Rahmi Nur Islami; Sulistya Rini Pratiwi; Meylin Rahmawati; Retno Dwi Arini (Journal of Applied Economics in Developing Countries, 2023)
Indonesia is one of the developing countries that is always trying to increase its economic growth. Indonesia has a large number of people with various ethnic backgrounds and diverse customs, so this situation has given rise to disparities between regions. This study aims to determine whether or not sigma convergence, to find out whether absolute and conditional convergence occurs or not, and to determine the speed of convergence. This study uses secondary data, namely Gross Regional Domestic Product (GRDP) per capita, poverty, and inequality for each province in Indonesia from 2017-2021. The method used in this study is panel data with a fixed effect approach. The results of the analysis using the sigma convergence (σ) approach show the occurrence of convergence. The results of the absolute convergence analysis explain the divergence of GRDP per capita in Indonesia with a divergence speed of 13.76% per year. The results of the conditional convergence analysis show that there is a divergence of GRDP per capita in Indonesia with a divergence speed of 13.62% per year.